Pengaruh Maturitas Sistem Pengendalian Intern Pemerintah Terhadap Kinerja Instansi Pemerintah - Ageng Gumelar; Iyeh Supriatna; Endah Dwi Kusumastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research was conducted to determine the effect of maturity of the government's internal control system on the performance of government agencies in the Purwakarta Regency Government. The population in this study is the Regional Work Unit (SKPD) in the Purwakarta Regency Government. The sample used in this study were 35 SKPDs in the Purwakarta Regency Government. The research method used is quantitative methods. The data source used is in the form of primary data. The data collection technique was carried out using research instruments in the form of questionnaires and interview guides. The data analysis method used is simple regression analysis. Result showed that the maturity of government internal control systems was positively and significantly affected by the performance of government agencies. With the increasing maturity of the government's internal control system, it can improve the performance of government agencies.